Effectiveness of aerobic exercise interventions on balance, gait, functional mobility and quality of life in Parkinson’s disease: an umbrella review - Yildirim Mehmet C.; Ekici Hatice S.; Collins Jemima; Piasecki Jessica; Skelly Rob; Gordon Adam L.; Phillips Bethan E. (Translational Exercise Biomedicine)
Parkinson’s disease (PD) is a neurodegenerative disorder with increasing prevalence into older age. Aerobic exercise (AE) is the most commonly prescribed exercise for PD, although an optimal protocol is undefined. This umbrella review aimed to summarise and synthesize existent evidence regarding the effectiveness of AE on balance, gait, functional mobility, and QoL in people with PD.